2009
DOI: 10.1007/s00442-009-1336-7
|View full text |Cite
|
Sign up to set email alerts
|

Placing biodiversity and ecosystem functioning in context: environmental perturbations and the effects of species richness in a stream field experiment

Abstract: Greater biodiversity is often associated with increased ecosystem process rates, and is expected to enhance the stability of ecosystem functioning under abiotic stress. However, these relationships might themselves be altered by environmental factors, complicating prediction of the effects of species loss in ecosystems subjected to abiotic stress. In boreal streams, we investigated effects of biodiversity and two abiotic perturbations on three related indices of ecosystem functioning: leaf decomposition, detri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 63 publications
2
54
0
1
Order By: Relevance
“…Our study highlights the importance of environmental context to explain the variability of results when examining biodiversity-ecosystem functioning relationships as found previously by others (Mckie et al 2009;Pascoal et al 2010). Manipulating 1-4 aquatic hyphomycete species, Pascoal et al (2010) showed that the exposure to zinc attenuated the positive effects of species richness on leaf decomposition.…”
Section: Discussionsupporting
confidence: 51%
“…Our study highlights the importance of environmental context to explain the variability of results when examining biodiversity-ecosystem functioning relationships as found previously by others (Mckie et al 2009;Pascoal et al 2010). Manipulating 1-4 aquatic hyphomycete species, Pascoal et al (2010) showed that the exposure to zinc attenuated the positive effects of species richness on leaf decomposition.…”
Section: Discussionsupporting
confidence: 51%
“…Flow reduction is also related to a decrease of the total taxa richness and shredder abundance (Death et al, 2009), which is also supported in our study. Species loss might impact ecosystem functioning by reducing the overall capacity of the biota to maintain a process at a given rate (McKie et al, 2009). Furthermore, as leaf litter decomposition in headwater streams represents the main input of energy within the system (Wallace et al, 1997), secondary species loss and further impairment of the ecosystem might easily be predicted in regulated headwater streams.…”
Section: Effects Of Dams On Structural Attributes Of the Reachmentioning
confidence: 99%
“…In contrast, by enclosing detritivores in litter-containing microcosms, Vos et al (2013) could distinguish between feeding on single and multiple litter species. Similar experiments would have to be conducted in streams (McKie et al 2009) to test whether consumermediated litter dissimilarity effects could arise at the stream-reach scale rather than at the litterbag scale examined in the present study.…”
Section: Environmental and Biological Constraints On Litter Diversitymentioning
confidence: 99%